Circulating tumor and invasive cell expression profiling predicts effective therapy in pancreatic cancer. Issue 15 (1st June 2022) - Yu, Kenneth H.; Park, Jennifer; Mittal, Avni; Abou‐Alfa, Ghassan K.; El Dika, Imane; Epstein, Andrew S.; Ilson, David H.; Kelsen, David P.; Ku, Geoffrey Y.; Li, Jia; Park, Wungki; Varghese, Anna M.; et al.
Abstract : Background: Pancreatic adenocarcinoma (PDAC) remains a refractory disease; however, modern cytotoxic chemotherapeutics can induce tumor regression and extend life. A blood‐based, pharmacogenomic, chemosensitivity assay using gene expression profiling of circulating tumor and invasive cells (CTICs) to predict treatment response was previously developed. The combination regimen of 5‐fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOLFIRINOX) and gemcitabine/nab‐paclitaxel (G/nab‐P) are established frontline approaches for treating advanced PDAC; however, there are no validated biomarkers for treatment selection. A similar unmet need exists for choosing second‐line therapy. Methods: The chemosensitivity assay was evaluated in metastatic PDAC patients presenting for frontline treatment. A prospective study enrolled patients ( n  = 70) before receiving either FOLFIRINOX or G/nab‐P at a 1:1 ratio. Six milliliters of peripheral blood was collected at baseline and at time of disease progression. CTICs were isolated, gene‐expression profiling was performed, and the assay was used to predict effective and ineffective chemotherapeutic agents. Treating physicians were blinded to the assay prediction results. Results: Patients receiving an effective regimen as predicted by the chemosensitivity assay experienced significantly longer median progression‐free survival (mPFS; 7.8 months vs. 4.2 months; hazard ratio [HR], 0.35; p  = .0002) and median overall survival (mOS; 21.0 months vs. 9.7 months; HR, 0.40; p  = .005), compared with an ineffective regimen. Assay prediction for effective second‐line therapy was explored. The entire study cohort experienced favorable outcomes compared with historical controls, 7.1‐month mPFS and 12.3‐month mOS. Conclusions: Chemosensitivity assay profiling is a promising tool for guiding therapy in advanced PDAC. Further prospective validation is under way (clinicaltrials.gov NCT03033927).